Experiences at the implementation of German courses in the IsF-program: Language policies, challenges and strategies - Voerkel, Paul Paul (Olhares & Trilhas, 2019)
Due to the investment undertaken since 2015, German institutions have become one of the main partners in the program Language without borders (IsF). This article contextualizes the growth of the German language IsF program and the increased academic cooperation between Germany and Brazil as a consequence of intentional Foreign Language Policy. After discussing the policy basics, the article presents the results of the two year trial period for German in the IsF program. The article concludes with a brief discussion of the German - Brazil plans for further academic cooperation in the field of IsF.